(untitled) (New York, 1994)
In a world where waste incinerators are not an option and landfills are at over capacity, cities are hard pressed to find a solution to the problem of what to do with their solid waste. Handbook of Solid Waste Management, 2/e offers a solution. This handbook offers an integrated approach to the planning, design, and management of economical and environmentally responsible solid waste disposal system
Sử dụng phế thải sinh học trong sản xuất phân hữu cơ
Keywords: Refuse and refuse disposal